PENGGUNAAN ANALYTICAL HIERARCHY PROCESS DALAM PENENTUAN KONSEP DESAIN LANSKAP WISATA DI DESA TIJAYAN - Melfrids Loisa Sumarauw; Alfred Jansen Sutrisno; Andree Wijaya Setiawan (MEDIAGRO, 2023)
Tijayan Village has natural and sociocultural potential as a tourist village. However, there is a lack of community understanding in developing this potential. Therefore, this research aims to determine the concept of landscape design using the Analytical Hierarchy Process (AHP) method. In designing the landscape of a tourist village, there are 4 aspects used, namely environmental, sociocultural, accessibility and facility aspects. However, it is necessary to determine the priority aspects of designing a tourist landscape. The AHP method is used to determine the priority value of each aspect by considering the experience and knowledge of experts, where the experts who become respondents are experts in the field of landscape architecture, and history and consider the opinions of the government and the people of Tijayan Village. The results showed that the sociocultural aspect (0.428) is the main priority in designing a tourist landscape in Tijayan Village, while the aspects of accessibility (0.202), facilities (0.189) and environment (0.182) are important but not the main ones. Thus, the concept of tourism village design requires a space that can fulfill the sociocultural aspects.